Analisis Kepuasan Pengguna MarketplaceTokopedia Dengan Metode PIECES di Tokopedia Community Batam - Muhamad Sigid Safarudin (Prosiding, 2018)
From year to year growth of household access to internet. Increase from 19.6% in 2013 to 36% in 2016. Internet users in Indonesia are using the internet in the field of economy.Tokopedia is one of the largest marketsplace in Indonesia. Marketplace that stands in 2009 has a seller growth of 30% per year. The popularity and the market of tokopedia users both as a buyer and as a seller does not provide satisfaction for the buyer or seller. The purpose of this research is to know the satisfaction of user with Pieces Methodology. The research instrument used questionnaires and online tools. Data analysis was using user satisfaction formula and categorize using level of user satisfaction from Kaplan and Norton's. Results for aspects of performance of 4.29, information aspects of 4.38, economic aspects of 4.49, control & security aspects of 4.59, efficiency aspects of 4.63 and the last aspect of service amounted to 4.33. The use of online tools performance throughput aspect was measured based on Pingdom 2 MB result, GT Metrix 3.26 MB and Webpagetest 3.31 MB. While the response time of Pingdom 6.08 s, GT Metrix 13.9 seconds and Webpagetest 16.625 s. Control & security aspects using Qualys SSL Labs online tools get an A and use CSTAR UpGuard score of 877. Respondents in this research are Tokopedia Community Batam members but only 30% of users use Tokopedia as the single platform.